Scale-up of radiotherapy for cervical cancer in the era of human papillomavirus vaccination in low-income and middle-income countries: a model-based analysis of need and economic impact. Issue 7 (July 2019) - Rodin, Danielle; Burger, Emily A; Atun, Rifat; Barton, Michael; Gospodarowicz, Mary; Grover, Surbhi; Hanna, Timothy P; Jaffray, David A; Knaul, Felicia M; Lievens, Yolande; Zubizarreta, Eduardo; Milosevic, Michael
Summary: Background: Radiotherapy is standard of care for cervical cancer, but major global gaps in access exist, particularly in low-income and middle-income countries. We modelled the health and economic benefits of a 20-year radiotherapy scale-up to estimate the long-term demand for treatment in the context of human papillomavirus (HPV) vaccination. Methods: We applied the Global Task Force on Radiotherapy for Cancer Control investment framework to model the health and economic benefits of scaling up external-beam radiotherapy and brachytherapy for cervical cancer in upper-middle-income, lower-middle-income, and low-income countries between 2015 and 2035. We estimated the unique costs of external-beam radiotherapy and brachytherapy and included a specific valuation of women's caregiving contributions. Model outcomes life-years gained and the human capital and full income net present value of investment. We estimated the effects of stage at diagnosis, radiotherapy delivery system, and simultaneous HPV vaccination (75% coverage) up to a time horizon set at 2072. Findings: For the period from 2015 to 2035, we estimated that 9·4 million women in low-income and middle-income countries required treatment with external-beam radiotherapy, of which 7·0 million also required treatment with brachytherapy. Incremental scale-up of radiotherapy in these countries from 2015 to meet optimal radiotherapy demand by 2035 yielded 11·4 million life-years gained, 59·3 billion in human capital net present value (−1·5 billion in low-income, 19·9 billion in lower-middle-income, and 40·9 billion in upper-middle-income countries), and 151·5 billion in full income net present value (1·5 billion in low-income countries, 53·6 billion in lower-middle-income countries, and 96·4 billion in upper-middle-income countries). Benefits increased with advanced stage of cervical cancer and more efficient scale up of radiotherapy. Bivalent HPV vaccination of 12-year-old girls resulted in a 3·9% reduction in incident cases from 2015–2035. By 2072, when the first vaccinated cohort of girls reaches 70 years of age, vaccination yielded a 22·9% reduction in cervical cancer incidence, with 38·4 million requiring external-beam radiotherapy and 28·8 million requiring brachytherapy. Interpretation: Effective cervical cancer control requires a comprehensive strategy. Even with HPV vaccination, radiotherapy treatment scale-up remains essential and produces large health benefits and a strong return on investment to countries at different levels of development. Funding: None.